Bio waste (Pistacia vera nut shell) filled polymer composites for tribological applications. (February 2022) - Pradhan, Subhrajit; Prakash, Ved; Acharya, Samir Kumar
The environmental concerns and quest for a sustainable future have encouraged the utilisation of bio-waste in a productive manner. In the present investigation, characterization studies such EDS, XRD and FTIR of pistacia vera (pistachio) nut shell particulates were carried out to have a knowledge of the morphological properties. Further, an attempt was made to utilise the bio-waste i.e. pistacia vera nut shell as a reinforcing phase in epoxy based polymer composites to assess the tribological behaviour of the fabricated composites. The pistachio shell particulate was incorporated with epoxy resin in different weight fractions (0, 10, 20 and 30%) to develop a new class of composite. The effect of filler content, normal load, sliding velocity and sliding distance on the two body abrasive wear behaviour of pistachio shell particulate reinforced epoxy composites was studied. The obtained results showed significant enhancement of abrasion resistance of the fabricated composites as compared to neat epoxy. Further, it was found that the composites with 20 weight percent of filler provide optimum abrasion resistance to the developed composite. The worn out surfaces of the composites were analysed using Scanning Electron Microscope to determine various failure mechanisms leading to deformation of the composite surface.